A design and implementation of performance dashboard for the work integrated learning unit - Pathathai Na Lumpoon (2020)
© 2019 IEEE. At present, the higher education institutes focus on the learning outcomes that curriculums can produce graduates with qualified employability skills. Work Integrated Learning (WIL) center is a unit in academic faculty that aims to develop students' competencies at workplace and classroom based on the integrated learning outcomes. However, measuring the performances of the WIL program is a difficult task such that the related key performance indicators are not identified. In this paper, we developed a novel model of the KPIs of WIL activities and the relevant employability skills. Additionally, design and implementation of the dashboards to display and monitor the defined KPIs are presented. As a result, users can gain insightful information and provide confidence for decision makers.